A decade of research on word formation in foreign language education: A scientometric mapping (2014–2024) - Nugraha, Danang Satria (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Word formation plays a crucial role in foreign language acquisition, enabling learners to expand their vocabulary and understand the meaning of unfamiliar words. However, a comprehensive understanding of the research landscape in this domain remains elusive. This study employed a scientometric approach to analyze the research landscape on word formation in foreign language teaching, utilizing data from the Scopus database spanning 2014 – 2024. Bibliographic and keyword analysis, facilitated by VOSviewer, was conducted on 240 documents to identify publication trends, major contributors, and thematic clusters. The findings reveal an escalating field, with a 333% increase in publications over the observed period and prominent contributions from journals such as “Russian Language Studies”, “Perspektivy Nauki i Obrazovania”, and “Xlinguae”. Four distinct thematic clusters were identified: (1) Cluster A (29.1%) encompassing foundational linguistic concepts and cognitive processes; (2) Cluster B (27.9%) focusing on pedagogical practices and learning processes; (3) Cluster C (23.3%) highlighting linguistic elements and acquisition challenges; and (4) Cluster D (19.8%) addressing the application and investigation of word formation knowledge. To some extent, this study provides an overview of recent research trends and informs future research directions in this crucial area of language learning and teaching.